2006
DOI: 10.1002/art.21572
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways regulating intercellular adhesion molecule 1 expression by endothelin 1: Comparison with interleukin‐1β in normal and scleroderma dermal fibroblasts

Abstract: Objective. Endothelin 1 (ET-1) has been implicated in the pathogenesis of fibrotic and inflammatory diseases, including scleroderma. In addition to modulating vascular tone and extracellular matrix turnover, ET-1 up-regulates cell surface adhesion molecules including intercellular adhesion molecule 1 (ICAM-1), which is key to cell-cell and cell-matrix adhesion and leukocyte infiltration. This study was undertaken to delineate the signal transduction pathways utilized by ET-1 and compare them with those adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…However, it should be taken into account that dermal fibroblasts may be a further source of increased serum levels of adhesion molecules. ICAM-1 expression on surface fibroblasts is modulated by ET-1 and inflammatory cytokines, is involved in cell–cell and cell–matrix interactions and plays a key role in regulating inflammatory cells binding to dermal tissue 23 24…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be taken into account that dermal fibroblasts may be a further source of increased serum levels of adhesion molecules. ICAM-1 expression on surface fibroblasts is modulated by ET-1 and inflammatory cytokines, is involved in cell–cell and cell–matrix interactions and plays a key role in regulating inflammatory cells binding to dermal tissue 23 24…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that ET B receptors located on vascular smooth muscle cells may mediate some of the pathological effects of ET-1 [54]. In addition, two studies have shown that the ET B receptor is important for adhesion molecule expression in endothelial and dermal cells [9,10]. In cardiovascular disease the ET B receptor may be upregulated [54,55], which could lead to it playing a greater role in the pathological effects of ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is a potent vasoconstrictor [7], but it is also pro-inflammatory [6], inducing vascular cell adhesion molecule (VCAM-1) expression, leukocyte adherence to endothelial cells, smooth muscle cell proliferation and arterial remodelling in vitro [8,9,10,11] and in vivo [4,5,12,13]. Furthermore, high plasma ET-1 levels correlate with raised soluble VCAM-1 levels in the blood of hypertensive patients and are associated with end organ damage [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ET B receptors, like ET A receptors, contribute to the pro-inflammatory action of ET-1: activation of the ubiquitous inflammatory mediator nuclear factor NFkB, increased vascular permeability, neutrophil adhesion, and cytokine release [Loomis et al, 2005;Waters et al, 2006;Wilson et al, 2001]. In transgenic mice, conditional cardiac overexpression of ET-1 in cardiac myocytes caused activation of NFkB, upregulation of the cytokines TNF-a, interleukin-1, interleukin-6, and interferon-g, and early death.…”
Section: Inflammationmentioning
confidence: 98%